2022
DOI: 10.3390/antiox11101991
|View full text |Cite
|
Sign up to set email alerts
|

Single and Combined Associations of Plasma and Urine Essential Trace Elements (Zn, Cu, Se, and Mn) with Cardiovascular Risk Factors in a Mediterranean Population

Abstract: Trace elements are micronutrients that are required in very small quantities through diet but are crucial for the prevention of acute and chronic diseases. Despite the fact that initial studies demonstrated inverse associations between some of the most important essential trace elements (Zn, Cu, Se, and Mn) and cardiovascular disease, several recent studies have reported a direct association with cardiovascular risk factors due to the fact that these elements can act as both antioxidants and pro-oxidants, depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 179 publications
0
7
0
Order By: Relevance
“…Currently, there is no consensus on which of the statistical methods is the best for mixture analysis. The purpose of QGC is to specifically address the inherent complexities of high-dimensional mixture data and to estimate the joint effect of the analyzed chemicals ( 24 ). BKMR can be used to find the nonlinear exposure–response relationship with other metals fixed at certain levels.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is no consensus on which of the statistical methods is the best for mixture analysis. The purpose of QGC is to specifically address the inherent complexities of high-dimensional mixture data and to estimate the joint effect of the analyzed chemicals ( 24 ). BKMR can be used to find the nonlinear exposure–response relationship with other metals fixed at certain levels.…”
Section: Discussionmentioning
confidence: 99%
“…For example, high Mn exposure could decrease the risk of high triglycerides ( 225 ), while elevated blood/serum levels of toxic heavy metals (such as Hg, As, and Pb) may increase the risk of different types of hyperlipidemia ( 226 228 ). Very recently, Barragán et al examined the associations of plasma essential trace elements with hyperlipidemia in a Mediterranean population, which demonstrated that plasma Mg concentrations and combined effect of plasma Zn, Cu, and Se levels had a positive association with hypercholesterolemia whereas plasma Mn concentrations would have negative effects on the amount of plasma lipids ( 229 , 230 ). A U-shaped link was suggested to exist between plasma Se levels and hypercholesterolemia, indicating that both low and high Se concentrations might have negative effects on plasma lipids ( 230 ).…”
Section: Recent Progress In Ionomics Of Metabolic Diseasesmentioning
confidence: 99%
“…Clinical analysis of heavy metal elements in human samples, such as serum, can provide information about occupational exposure, intake, and toxicity of heavy metals and can also be used for the diagnosis of some diseases [ 7 10 ]. With the development of environmental epidemiology and exposure omics, researchers have become increasingly interested in the relationship between trace elements and chronic non-communicable diseases in the general population [ 11 13 ], which requires the establishment of a series of element detection methods.…”
Section: Introductionmentioning
confidence: 99%